Colonoscopy ‘My Way’: Preparation, Anticoagulants, Antibiotics and Sedation - Jerome D Waye (Canadian Journal of Gastroenterology)
Colonoscopy was introduced in the 1960s. The facility with which this technique is performed has been enhanced by vast improvements in instrumentation. In spite of this, physician attitudes concerning colonoscopy have changed little over the past several decades. The diet for precolonoscopic preparation has not been altered for 30 years. Colonoscopists have a great reluctance to use a new preparation instead of the 4 L electrolyte solution, perhaps because this was such a significant advance in colonoscopic cleansing, its predecessor being castor oil and enemas. Physicians continue to be wary of the patient who is taking acetylsalicylic acid in the absence of any studies that show that this is detrimental for polypectomy. The management of the patient on warfarin anticoagulation remains a subject for debate. As for antibiotic prophylaxis, most endoscopy units do not have a standardized approach, although there are good guidelines that, if followed, should decrease the risk of infective endocarditis. Sedation for the endoscopic examination is usually administered by the colonoscopist, although anesthesiologists may, in some countries (and in some defined areas of the United States) be the primary administrators of sedation and analgesia. The present article is a personal approach to the following issues: the preparation of the colon for an examination, current thoughts about anticoagulation and acetylsalicylic acid, antibiotic prophylaxis for colonoscopy and the technique for sedation out of the hospital.